Instructional design complexity and pop-up notification interference: effects on attention allocation and information retention in virtual classrooms - Wang, Yushan (Frontiers in Psychology, 2025)
The growing prevalence of virtual multimedia learning environments raises questions about how instructional complexity and environmental interference jointly shape learning. This study examines the independent and interactive effects of instructional design complexity (IDC) and pop-up notification interference (PNI) on attention allocation and information retention. IDC was manipulated through instructional design, using streamlined layouts with concise text (low complexity) versus fragmented layouts with redundant on-screen text and background audio (high complexity). PNI (external-to-material) was manipulated through the presence or absence of periodic, task-irrelevant pop-up notifications. Drawing on Cognitive Load Theory (CLT), the Limited Capacity Model of Mediated Message Processing (LC4MP), and Media Multitasking Theory (MMT), a 2 × 2 between-subjects experiment was conducted with 240 Chinese undergraduates. Both IDC and PNI had significant adverse main effects, and their combination produced the lowest attention and retention scores. Structural equation modeling revealed that attention allocation partially mediated the relationship between the two factors and retention performance. Moderation analysis showed that learners with greater digital learning experience were less affected by PNI. This research advances CLT in ecologically valid digital contexts. It offers actionable design principles for creating distraction-resilient, cognitively sustainable virtual learning environments by integrating process-level attention metrics with clearly defined dual-factor manipulations.